Safety profile of herbal drugs: urgent need for monitoring - Palaian, S; Mishra, P; Bista, D; Rajan, S; Shankar, P Ravi (Journal of Institute of Medicine Nepal, 2007)
Background: In developing countries, herbal medicines are the natural answer to many ailments and are often locally available in affordable cost. Hence, their use remains popular and widespread in many countries. Due to the varying topography and climatic conditions, a variety of herbs and medicinal plants are found in Nepal. The public generally considers natural products as safe. Also, the manufacture, sale, distribution and use of these medicines are not monitored by the regulatory authorities. Doctors also don’t routinely take drug history regarding use of herbal drugs. Several commonly used herbal drugs like gingko biloba, garlic, ginseng, peppermint oil, senna, primrose oil, isapghol, ephedra are reported to cause significant adverse drug reactions which can cause mild gastrointestinal upset to life threatening bleeding disorders. The safety concern regarding allopathic drugs is strengthening and the awareness regarding this issue is increasing rapidly. However, monitoring the safety of herbal drugs is still problematic due to various reasons. Some of reasons are lack of accurate information regarding their safety profile, lack of information on the exact constituents of the conventional herbal formulations, adulteration in the drug formulations, poor manufacturing standards etc. Conclusion: Team efforts involving doctors, pharmacists, pharmacologists, pharmacovigilance center personnel and drug regulatory authorities will be beneficial in implementing appropriate steps towards safe use of herbal drugs. The participation of patients and the manufacturers is also vital. Worldwide, many initiatives have been taken in the recent past towards herbal drug safety. In Nepal the concept of drug safety issues is still in the infancy stage and the national drug controlling authority has taken the initial steps in monitoring the safe use of allopathic drugs. The need for an herbal drug safety monitoring system is very essential for a country like Nepal. Key words: Herbal drug, safety profile, monitoring. The full text of this paper is available at Journal of Institute of Medicine website